2016
DOI: 10.1038/srep35321
|View full text |Cite
|
Sign up to set email alerts
|

New Insecticidal Agents from Halogenation/Acylation of the Furyl-Ring of Fraxinellone

Abstract: Introduction of the halogen atom or the acyl group at the C-ring of fraxinellone was investigated. Some unexpected halogenation products were obtained with the different chlorination/bromination reagents, and their possible reaction mechanisms were also proposed. Seven key steric structures of 2a’, 2b, 2b’, 2c’, 3a, 3b, and one isomer (5’α-Cl) of 2a were further confirmed by single-crystal X-ray diffraction. Especially compounds 2a, 2a’, 3a and 3c exhibited more potent insecticidal activity than toosendanin. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The furan ring of fraxinellone ( 1 ) was previously brominated at the C-2′ and C-5′ positions using NBS (Fig. 2 ) 34 ; however, these reaction conditions produced either low or highly variable yields. In order to optimize the reaction conditions to obtain the monobromofraxinellone or dibromofraxinellone selectively in a higher yield, a reduced fraxinellone ( 2 ) was used as the starting material for excluding the possible effect of C-2 and C-3 double bonds in the NBS bromination reaction of 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The furan ring of fraxinellone ( 1 ) was previously brominated at the C-2′ and C-5′ positions using NBS (Fig. 2 ) 34 ; however, these reaction conditions produced either low or highly variable yields. In order to optimize the reaction conditions to obtain the monobromofraxinellone or dibromofraxinellone selectively in a higher yield, a reduced fraxinellone ( 2 ) was used as the starting material for excluding the possible effect of C-2 and C-3 double bonds in the NBS bromination reaction of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they also reported that fraxinellone-based esters and hydrazones derivatives at C-4/C-10 position (A-ring) displayed higher insecticidal activity 31 33 . In contrast, the lack of chemical handle on the furan ring has limited the derivatives with the furan ring intact to only a few examples 34 . Since the importance has implicated the furan ring, such derivatives would be useful in elucidating additional SAR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our program to discover new natural-product-based insecticidal agents, by using podophyllotoxin ( 1 , Figure a), a sustainable naturally occurring cyclolignan isolated from Juniperus Sabina (widely distributed in northwestern China), as a lead compound, we prepared a series of 4α-acyloxy-2′(2′,6′)-(di)­halogenopodophyllotoxin derivatives ( 2 , Figure a) . They mainly showed the potent growth inhibitory activity against third-instar larvae of M. separata as we reported other natural-product-based insecticidal agents such as obacunone and fraxinellone. , When compared with that of the blank control (33 days), the growth duration from the third-instar larva to moth was shortened to 30 days in the treated groups. Interestingly, many malformed moths with imperfect wings in the treated groups appeared during the stage of adult emergence (Figure b) .…”
Section: Introductionmentioning
confidence: 99%
“…1). Yet, the lack of furan-site chemical handle has limited the furan-site diversity of NPs [19]. Obacunone ( 1 , Fig.…”
Section: Introductionmentioning
confidence: 99%